The Impact of Brand Value towards Stock Price in Indonesian Banking Industry - Valdi Vallian (iBuss Management, 2015)
Brand value is especially important in banking industry, because it enables firms to get recognition from customers as well as gaining loyalty, which is pivotal in determining firms’ success. The purpose of this research is to determine whether brand value affects company performance in the form of stock price. The research is conducted over four biggest banks in Indonesia in terms of market capitalization in Indonesian, namely Bank BCA, Bank Mandiri, Bank Danamon, and Bank BRI, which are observed over eight years of operation  (2007-2014). Multiple linear regression method was used in this research, with the stock price as dependent variable and brand value, along with three financial performance indicators as the independent variable. The results of the research indicate that in Indonesian Banking Industry, brand value does not significantly affect stock price, at least individually. Instead, Earnings per Share is found to be the only significant impacting variable towards stock price.   Keywords: brand value, stock price, multiple linear regression, Indonesian banking industry